FROM COMPREHENSION QUESTIONS TO COMMUNICATIVE OUTCOMES: RETHINKING LISTENING ASSESSMENT IN TBLT - Mardona Rakhimova, (TADQIQOTLAR, 2026)
Abstract Listening assessment in many English language classrooms remains dominated by  comprehension-based  questions  that  prioritize  discrete-item  understanding  over communicative ability. This paper argues that such practices are misaligned with the principles  of  Task-Based  Language  Teaching  (TBLT),  which  emphasize  meaning-focused  communication  and  real-world  language  use.  Drawing  on  key  theoretical frameworks in TBLT and listening pedagogy, the paper critiques traditional listening assessment formats and proposes a shift toward communicative, task-based outcomes. Practical examples of alternative assessment models are provided, highlighting how listening can be evaluated through interaction, decision-making, and performance. The paper  concludes  that  rethinking  listening  assessment  is  essential  for  developing learners’ functional communicative competence.